Association of extracerebral organ failure with 1-year survival and healthcare-associated costs after cardiac arrest: an observational database study - Pekkarinen PT; Backlund M; Efendijev I; Raj R; Folger D; Litonius E; Laitio R; Bendel S; Hoppu S; Ala-Kokko T; Reinikainen M; Skrifvars MB (BMC, 2022)
BackgroundOrgan dysfunction is common after cardiac arrest and associated with worse short-term outcome, but its impact on long-term outcome and treatment costs is unknown.MethodsWe used nationwide registry data from the intensive care units (ICU) of the five Finnish university hospitals to evaluate the association of 24-h extracerebral Sequential Organ Failure Assessment (24h-EC-SOFA) score with 1-year survival and healthcare-associated costs after cardiac arrest. We included adult cardiac arrest patients treated in the participating ICUs between January 1, 2003, and December 31, 2013. We acquired the confirmed date of death from the Finnish Population Register Centre database and gross 1-year healthcare-associated costs from the hospital billing records and the database of the Finnish Social Insurance Institution.ResultsA total of 5814 patients were included in the study, and 2401 were alive 1year after cardiac arrest. Median (interquartile range (IQR)) 24h-EC-SOFA score was 6 (5-8) in 1-year survivors and 7 (5-10) in non-survivors. In multivariate regression analysis, adjusting for age and prior independency in self-care, the 24h-EC-SOFA score had an odds ratio (OR) of 1.16 (95% confidence interval (CI) 1.14-1.18) per point for 1-year mortality.Median (IQR) healthcare-associated costs in the year after cardiac arrest were Euro47,000 (Euro28,000-75,000) in 1-year survivors and Euro12,000 (Euro6600-25,000) in non-survivors. In a multivariate linear regression model adjusting for age and prior independency in self-care, an increase of one point in the 24h-EC-SOFA score was associated with an increase of Euro170 (95% CI Euro150-190) in the cost per day alive in the year after cardiac arrest. In the same model, an increase of one point in the 24h-EC-SOFA score was associated with an increase of Euro4400 (95% CI Euro3300-5500) in the total healthcare-associated costs in 1-year survivors.ConclusionsExtracerebral organ dysfunction is associated with long-term outcome and gross healthcare-associated costs of ICU-treated cardiac arrest patients. It should be considered when assessing interventions to improve outcomes and optimize the use of resources in these patients.